Enhancing Financial Reporting Quality to Improve Investment Efficiency (Empirical Evidence from Companies Listed in Indonesia Stock Exchange) - Fettry, Sylvia; Djuitaningsih, Tita (International Journal of Economics, Business and Management Studies, 2019)
This study is aimed to gain insight about the investment efficiency in companies listed in Indonesia Stock Exchange as emerging market. Company’s investment efficiency has important role in the economic growth. Based on the theoretical framework, the high quality of financial reporting will improve the confidence level of decision making in investment. So that, enhancing the financial reporting quality will make the better investment efficiency. This study is conducted to get empirical evidence on the effect of enhanced financial reporting quality on investment efficiency. The secondary data source are the current annual financial statement of companies listed in Indonesia Stock Exchange from various industries. Financial reporting quality is assessed by the level of qualitative characteristic of financial statement. The deviation level of expected investment is used as the measurement of investment inefficiency. This study uses purposive sampling with the criteria used are the willingness of the company to provide an explanation of the process of financial reporting and investment in several focus group discussions. Multiple regression is used to analyze the data for hypothesis testing. The result shows that enhancing financial reporting quality will improve the investment efficiency in the Indonesian companies context. Good financial reporting will produce a good financial statement. Good financial statement will support management’s decision making to invest in more efficient way. In the Indonesia companies context, investment ineffiency are still incurred. Underinvestment and overinvestment become common practices in companies listed in Indonesia Stock Exchange.